Psychosocial factors and their association with reflux oesophagitis, Barrett’s oesophagus and oesophageal adenocarcinoma - Denver, Paul (Baishideng Publishing Group Co., Limited, 2013)
AIM: To investigate the role of psychological characteristics as risk factors for oesophageal adenocarcinoma (OAC), as well as the reflux-mediated precursor pathway. METHODS: An all-Ireland population-based case-control study recruited 230 reflux oesophagitis (RO), 224 Barrett’s oesophagus (BO) and 227 OAC patients and 260 controls. Each case/control group completed measures of stress, depression, self-efficacy, self-esteem, repression and social support. A comparative analysis was undertaken using polytomous logistic regression adjusted for potential confounders. RESULTS: Compared to controls, OAC patients were almost half as likely to report high stress levels over their lifetime (P = 0.010, OR 0.51; 95%CI: 0.29-0.90) and 36% less likely to report having experienced depression (OR 0.64; 95%CI: 0.42-0.98). RO patients reported significantly higher stress than controls particularly during middle- and senior-years (P for trends < 0.001). RO patients were 37% less likely to report having been highly emotionally repressed (OR 0.63; 95%CI: 0.41-0.95). All case groups (OAC, RO and BO) were more likely than controls to report having had substantial amounts of social support (OR 2.84; 95%CI: 1.63-4.97; OR 1.97; 95%CI: 1.13-3.44 and OR 1.83; 95%CI: 1.03-3.24, respectively). CONCLUSION: The improved psychological profile of OAC patients may be explained by response shift. The role of psychological factors in the development of OAC requires further investigation.